Coupled Transport of Sulfate and Chloride Ions With Adsorption Effect: A Numerical Analysis - Xu, Jun; Mo, Rui; Wang, Penggang; Zhou, Jiguo; Dong, Xiaojin; She, Wei (Frontiers in Materials, 2020)
In the marine environment, reinforced concrete will suffer from chloride ion erosion and sulfate ion erosion at the same time. However, most scholars only study the interaction mechanism between chloride ion and sulfate ion, and the consideration of physical adsorption and chemical combination caused by hydration products is not perfect. Based on the law of conservation of mass, this study integrates the relationship between porosity and hydration time, the weakening of chemical binding of sulfate ions to chloride ions into the mathematical model, establishes the coupling transport model of sulfate and chloride, and verifies the rationality of the model by comparing with the measured data. And then, the physical adsorption and chemical binding of chloride ions under the action of sulfate ions were quantitatively analyzed. It is found that chemical binding is dominant and sulfate ion will reduce the chemical binding effect of chloride ion. With the decrease of the initial water/cement ratio, the diffusion depth of free chloride ion will also decrease.